Value-chain analysis of the ginger sub-sector in Salyan District, Nepal - ACHARYA, NOBEL; CHAURASIA, JAY; KANDEL, PARBATI (Asian Journal of Agriculture, 2023)
Abstract. Acharya N, Chaurasia J, Kandel P. 2023. Value-chain analysis of the ginger sub-sector in Salyan District, Nepal. Asian J Agric 7: 76-82. A Value Chain (VC) strategy of market-driven firms is required to solve the present shortcomings in ginger's marketing channel and the ensuing value addition throughout the channel. The study examines ginger's producer share, pricing spread, marketing margin, and value-chain diagram. Furthermore, 50 producer families from each of Malneta of Sharada Municipality and Chande of Siddhakumakh Rural Municipality in Salyan District, Karnali Province, Nepal were selected for the household survey using purposive random sample based on the degree of production and producers' cultivation of ginger in more than one ropani, i.e., total 100 households, five collectors, five wholesalers, and five retailers were surveyed for analysis. The total ginger productivity at the research location was 15.43 Mt/ha. Sutho (dried ginger) earned an average of 25.81% of the earnings. Furthermore, 100% of producers said they were satisfied with the low price but higher than the farms' gate price by NPR 24. There was an NPR disparity of NPR 8 in retail marketing costs between retailers and end users, and NRs gap of NPR6 in marketing costs between wholesaler and retailer. While the difference in marketing costs between the collector and the distributor was, NPR 6. Retailers and consumers had the largest net margin (20%), which collectors and wholesalers followed. Consumer pricing was (8.3%), wholesalers and retailers (6.66%) and the producer share was calculated to be just 40%.
Keywords: Disparity, net margin, producer share, sutho, value chain